Observational Play Assessment in Recreational Therapy (OPART): A case study for the validation of assessments in recreational therapy - Fox, BS, Nicole Christine; Loy, PhD, CTRS/LRT, David P. (American Journal of Recreation Therapy, 2019)
As a growing occupation, it is critical that recreational therapy (RT) assessments are evaluated to provide evidence of the effectiveness of treatment. This study analyzed the interrater reliability, convergent validity, and predictive validity of a new RT Assessment, the Observational Play Assessment in Recreational Therapy (OPART). The assessment was designed to provide the opportunity to assess levels of physical, cognitive, emotional, and social skills of children with developmental disabilities while observed in play settings. Reliability and validity evidence was generated through the comparison of the OPART to an established assessment used in RT, the Comprehensive Evaluation in Recreation Therapy. Results suggested the OPART had some very preliminary psychometric evidence. While promising, it is clear that significant development and validation is further indicated. The more important value of this article may be its’ use as a model of ways to validate new RT assessments in the field.